PENDEKATAN KONTRUKTIVIS SOSIAL DALAM PEMBELAJARAN - Saarah Shafa Salsabila; Septi Gumiandari (EDUCATIONAL JOURNAL : General and Specific Research, 2024)
The social constructivist approach is a learning paradigm that emphasizes the role of social interaction in building students' knowledge and understanding. This approach highlights the importance of collaboration, dialogue and joint activities between teachers and students, as well as between students, as a way to build knowledge together. In social constructivist learning, knowledge is not only viewed as information conveyed by the teacher, but as the result of a joint construction process through social interaction. Social constructivist learning promotes active and participatory learning, where students not only receive information but are also involved in constructing their own understanding through discussions, questions and answers, and group activities. Teachers act as learning facilitators who encourage students to think critically, stimulate the exchange of ideas, and construct knowledge together. The importance of the social constructivist approach lies in its ability to build deep understanding, increase student engagement, and develop social and cognitive skills. By placing an emphasis on social interaction, this approach creates a learning environment that supports students' cognitive growth and social development. Therefore, the implementation of social constructivism in an educational context can increase the effectiveness of learning and prepare students to face future challenges.